Analisis Manajemen Dana Desa Terhadap Pembangunan di Desa Tantan - Elsa Wirda Yanti; As’ad Isma; Eja Armaz Hardi (Jurnal Riset dan Inovasi Manajemen, 2023)
In managing village funds, the government in Tantan Village has limited human resources that have a role in managing them. Based on its type, this research is a qualitative research with primary and secondary data sources. The methods used for data collection in this study are observation, interviews, and documentation. The steps in the analysis are collecting data, summarizing the data, presenting the data, and then drawing conclusions. Based on the results of this study, it shows that the management of village funds under development in 2021 at the planning, implementing, organizing, implementing and also reporting stages has been carried out quite well. In an Islamic perspective, the management of village funds in Tantan village has not yet implemented the principle of justice in its implementation. And for the impact arising from the management of village fund management in the village of Tantan, it is felt that it has had a positive impact in the field of development.